Droughts, flooding events, and shifts in water sources and seasonality characterize last interglacial Levant climate. (15th November 2020) - Kiro, Yael; Goldstein, Steven L.; Kushnir, Yochanan; Olson, Jennifer M.; Bolge, Louise; Lazar, Boaz; Stein, Mordechai
Abstract: Modern observations document increased drought frequency together with more intense precipitation and flooding in the world's semi-arid and arid regions as a consequence of the warming climate. Climate models predict that such conditions will intensify in the future, impacting millions of people. Paleoclimate studies can complement the short modern observational record and model projections by documenting climate changes in the past. Here we report major shifts in the geographic sources, intensity, and seasonality of Eastern Mediterranean precipitation during the unusually warm last interglacial period Marine Isotope Stage (MIS) 5e, reflecting global shifts in the rain and desert belts, based on 234 U/ 238 U-ratios in mineral precipitates in the Dead Sea, combined with evidence from climate model simulations. In the Dead Sea catchment 234 U/ 238 U ratios are indicators of water sources, where the Jordan River (flowing from the north) and the western catchments show high activity ratios between ∼1.5–1.7, and the eastern and southern catchments and flash floods (in the south-west, south and east) show lower ratios of 1.0–1.2. In Dead Sea water and precipitated minerals, 234 U/ 238 U is nearly always ∼1.45–1.55 during both glacials and interglacials. However, during the last interglacial MIS 5e insolation peak (∼127–122 ka) its value decreased to 1.2–1.3, and then to ∼1.0 towards its end (∼122–116 ka). During the insolation peak, the U-isotope data, combined with climate model runs forced with period orbital and greenhouse gas concentrations, indicate that rainfall associated with the African Summer Monsoon in the Dead Sea catchment accounted for ∼50% of the total annual rainfall, in stark contrast to present-day dry summers. The geochemical evidence indicates that following the insolation peak the region experienced an extremely dry period (although punctuated with wetter intervals), signifying expansion of the desert belt, similar to predicted effects of anthropogenic warming. This drying is partly supported by climate model runs forced with the appropriate changes in orbital parameters. The extreme drying during late MIS 5e between ∼122–116 ka reflected a major weakening of Mediterranean storm systems, resulting in a major decline of the Jordan River flow (indicated by the low 234 U/ 238 U ratios in the Dead Sea) and a relative increase in precipitation associated with the African Monsoon, shifting towards autumn. The Jordan River flow is estimated to be ∼10% of the present-day (pre-1964, prior to major diversion of the Jordan River and its sources for human use). Such changes, if they occur in the future, have serious implications for future water availability in the politically sensitive Middle East. Highlights: New 234 U/ 238 U proxy for water sources. Effect of tropical rainfall on Levant climate recorded in the Dead Sea. Drought associated with flooding at the end of the last interglacial.